Two clones of N1 gene derived from isolate A/Dk/Tangerang/Bbalitvet-ACIAR-TE11/2007 (H5N1) exhibit single mismatch of amino acid sequence at position 242 that is threonine and methionine for the clone #3 and #5, respectively. In order to evaluate the effect of the amino acid substitution, these clones were inserted into two different expression vectors that are pEGFP-C1 and pcDNA-3.3 TOPO® TA cloning. Subsequently, the respective recombinant clones were transfected into eukaryotic cells, includi - RISZA HARTAWAN; NI LUH PUTU INDI DHARMAYANTI; KARL ROBINSON; TIMOTHY MAHONY; JOANNE MEERS (HAYATI Journal of Biosciences, 2012)
Two clones of N1 gene derived from isolate A/Dk/Tangerang/Bbalitvet-ACIAR-TE11/2007 (H5N1) exhibit single mismatch of amino acid sequence at position 242 that is threonine and methionine for the clone #3 and #5, respectively. In order to evaluate the effect of the amino acid substitution, these clones were inserted into two different expression vectors that are pEGFP-C1 and pcDNA-3.3 TOPO® TA cloning. Subsequently, the respective recombinant clones were transfected into eukaryotic cells, including CEF, RK13 and VERO using Lipofectamine ‘plus’ reagent. As a result, the clone #3 retaining atypical sequence showed lower expression level rather than the clone #15 in both vectors and all type of cells. The 3D conformational modelling revealed that the mutation occurs in the inner part of glycoprotein embedded within envelope or matrix. Therefore, the missense mutation seems has no effect on the antigenic properties of neuraminidase but this substitution by any means causes lethal mutagenesis in the individual gene expression by reducing level of protein transcript.